2018
DOI: 10.1177/0022343318777566
|View full text |Cite
|
Sign up to set email alerts
|

Aid, exclusion, and the local dynamics of insurgency in Afghanistan

Abstract: Can developmental aid bring peace to war-torn communities? The current literature is divided on this issue. One line of reasoning suggests that aid is likely to decrease violence by improving employment and prosperity, thereby making participation in conflict more costly. Another view cites evidence showing an association between aid projects and increased insurgent activity. Addressing this contradiction, we argue that different types of aid projects lead to different outcomes, as some projects foster an uneq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…In addition, future research should disaggregate ODA grants and further elaborate whether and how different types of foreign aid influence conflicts in disasteraffected countries. Different types of aid can generate diverse effects in the disaster-conflict nexus owing to various factors, such as differences in timing (Clemens et al, 2012), different donor preferences regarding channeling through state or nonstate actors (Dietrich, 2013), and the exclusivity of aid among recipients (Karell and Schutte, 2018). The study of natural disasters, foreign aid, and civil conflict is complex because the combinations of different types of natural disasters and aid could have diverse impacts on civil conflict initiation, duration, and termination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future research should disaggregate ODA grants and further elaborate whether and how different types of foreign aid influence conflicts in disasteraffected countries. Different types of aid can generate diverse effects in the disaster-conflict nexus owing to various factors, such as differences in timing (Clemens et al, 2012), different donor preferences regarding channeling through state or nonstate actors (Dietrich, 2013), and the exclusivity of aid among recipients (Karell and Schutte, 2018). The study of natural disasters, foreign aid, and civil conflict is complex because the combinations of different types of natural disasters and aid could have diverse impacts on civil conflict initiation, duration, and termination.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on Syria suggest that strategies to address climate and water-related conflict risks should be multi-layered processes intersecting with social and economic policies 32 Karell and Schutte (2018) found that aid exacerbates conflict if it leads to exclusionary projects.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on Gamso and Yuldashev (2018), I further argue that it is not the dichotomous presence or absence of conflict that matters, but rather its intensity. Finally, following a number of studies on the local impact of development projects (Sexton 2016;Karell and Schutte 2018), as well as conflict research on the subnational dynamics of violence (Williams et al 2012;Nyseth Brehm 2017), I argue that these processes unfold locally. In sum, I hypothesize that in developing countries, the intensity of conflict experience in a given community should lead to increased out-migration from that community, even after the war has ended, but that this relationship is moderated by local reconstruction efforts.…”
Section: Reconstruction and Migrationmentioning
confidence: 97%